(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Autoimmune vesiculobullous disorders are chronic, relapsing illnesses that are associated with significant morbidity due to prolonged corticosteroid use. Rituximab is an important steroid-sparing drug, the optimal dose of which is still poorly understood, particularly in resource-limited areas. Method: A retrospective comparative effectiveness study was conducted to assess low dose (LD) versus standard dose (SD) rituximab in patients with moderate to severe autoimmune vesiculobullous conditions. Low dose (LD) versus standard dose (SD) rituximab was evaluated in a retrospective comparative effectiveness study for moderate to severe autoimmune vesiculobullous disorders. A total of 72 patients were analyzed, 36 of which were treated with low dose rituximab (500 mg on days 1 and 15) and 36 were treated with standard dose rituximab (1000 mg on days 1 and 15). Primary outcomes were the proportion of patients achieving disease control at week 8 and complete remission after minimal therapy at 12 months. Secondary outcomes were time to disease control, cumulative prednisolone dosage, relapse, adverse events and direct drug cost. Results: The results showed that 30 (83.3%) of the 36 patients in the low-dose group and 33 (91.7%) of the 36 patients in the standard-dose group achieved disease control by week 8 (p=0.47). The two groups had rates of 66.7% and 75.0% complete remission at minimal therapy at 12 months, respectively, with no significant difference (p=0.44). Conclusions: The standard dose rituximab resulted in slightly more rapid disease control, whereas the low dose dose resulted in a 50.0% decrease in direct cost of rituximab and had fewer infusion reactions. There was no significant difference in relapse rates. In some vesiculobullous disorders, low-dose rituximab could prove effective, safer and more cost-effective, but there is a need for individual risk assessment and longer follow-up.